2001
DOI: 10.1051/0004-6361:20010006
|View full text |Cite
|
Sign up to set email alerts
|

NaI and HI 3-D density distribution in the solar neighbourhood

Abstract: Abstract.A study of the local interstellar medium (LISM) using a robust inversion method, similar to current tomography techniques, is applied to compiled data on neutral interstellar absorbers and Hipparcos parallaxes. We present here the 3-D distribution of two neutral species, NaI and HI. Our analysis enables us to obtain a reliable 3-D density distribution of the IS matter in the solar neighbourhood, providing a new basis for the discussion of origin, present state and evolution of the LISM. We show that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
98
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 18 publications
3
98
0
Order By: Relevance
“…Using these data, together with NaI absorption measurements towards a further ∼240 nearby targets published in the literature (for many of them, in the directions of molecular clouds), and the ∼450 linesof-sight already presented by , we show 3D absorption maps of the local distribution of neutral gas towards 1005 sight-lines with Hipparcos distances as viewed from a variety of different galactic projections. The data are synthesized by means of two complementary methods, (i) by mapping of iso-equivalent width contours, and (ii) by density distribution calculation from the inversion of column-densities, a method devised by Vergely et al (2001). Our present data confirms the view that the local cavity is deficient in cold and neutral interstellar gas.…”
supporting
confidence: 68%
“…Using these data, together with NaI absorption measurements towards a further ∼240 nearby targets published in the literature (for many of them, in the directions of molecular clouds), and the ∼450 linesof-sight already presented by , we show 3D absorption maps of the local distribution of neutral gas towards 1005 sight-lines with Hipparcos distances as viewed from a variety of different galactic projections. The data are synthesized by means of two complementary methods, (i) by mapping of iso-equivalent width contours, and (ii) by density distribution calculation from the inversion of column-densities, a method devised by Vergely et al (2001). Our present data confirms the view that the local cavity is deficient in cold and neutral interstellar gas.…”
supporting
confidence: 68%
“…The first computed tomography of the local ISM from Vergely et al (2001) used neutral sodium absorption data combined with Hipparcos stellar parallaxes (Perryman et al 1997) and a tomographic method based on the work of Tarantola & Valette (1982a), specifically applied for the first time to extinction by the ISM by Chen et al (1998). This type of tomography is a new manner to represent the ISM, considering it as a continuous medium without a priori cloud discretization and considering the clouds and the voids as fluctuations around a median density, the "prior" value.…”
Section: Introductionmentioning
confidence: 99%
“…This type of tomography is a new manner to represent the ISM, considering it as a continuous medium without a priori cloud discretization and considering the clouds and the voids as fluctuations around a median density, the "prior" value. Lallement et al (2003) presented additional sodium observations especially dedicated to the Local Bubble boundary determination, recorded during several observing programs, and made use of about 1000 carefully screened data for a column density mapping and a tomography based on the same algorithm as in Vergely et al (2001). An updated study using about 1700 targets as well as the first tomography using ionized calcium are presented in the recent study by Welsh et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore this lowcolumn density uncertainty is not important considering the M7 and negligible for the intended population synthesis with neutron stars (NSs) at usually larger distances. Vergely et al (2001) could not always find a correlation of the Nai density with the H i density. They concluded that the correlation is rather weak due to non-constant population ratios for interstellar medium species, thus different abundances.…”
Section: The Inhomogeneously Distributed Ismmentioning
confidence: 79%
“…Breitschwerdt 1998). The most detailed view is provided by the study of Lallement et al (2003), who measured Na i absorption towards 1005 sightlines with Hipparcos distances up to 350 pc from the Sun; for more details on the measurements and the applied density inversion method see Lallement et al (2003), the precursor paper Sfeir et al (1999), andVergely et al (2001). Nai is regarded as good tracer of the total amount of the neutral interstellar gas and the sodium column density is thought to be convertable into a hydrogen column density (e.g.…”
Section: The Inhomogeneously Distributed Ismmentioning
confidence: 99%